Self-Assembled Redox Polyelectrolyte-Surfactant Complexes: Nanostructure and Electron Transfer Characteristics of Supramolecular Films with Built-In Electroactive Chemical Functions - Cortez, María Lorena (2013)
The mesostructural and electrochemical characterization of a redox-active polyelectrolyte-surfactant complex formed by polyallylamine tagged with an osmium complex and dodecylsulfate is presented. X-ray reflectivity (XRR), grazing-incidence small-angle X-ray scattering (GISAXS), X-ray photoelectron spectroscopy (XPS), contact angle goniometry (CA) and cyclic voltammetry (CV), including the numerical simulation of the voltammetric response, were employed to analyze the structure, stability and the electrochemical response of these supramolecular films. In contrast to redox-active polyelectrolyte multilayers (PEMs), the self-assembled system presented here shows a mesoscopic order yielding a film of layered structure very stable to an aqueous environment where the hydrophilic moieties (amino and sulfate groups) are not exposed to the solution since a contact angle of 95º is observed upon exposure to water. However, the film shows a self-exchange electron transfer mechanism with an apparent diffusion coefficient of 2x10-9 cm2 s-1 for a film of 300 nm of thickness. This behavior shows that the film exposed to an aqueous solution undergoes a fast electron transfer process to/from the electrode surface and ions to/from the electrolyte solution.